Comprehensive analysis of F8 large deletions: Characterization of full breakpoint junctions and description of a possible DNA breakage hotspot in intron 6. (16th August 2022) - Jourdy, Yohann; Chatron, Nicolas; Fretigny, Mathilde; Dericquebourg, Amy; Sanlaville, Damien; Vinciguerra, Christine
Abstract: Background: Large F8 deletions represent 3–5% of the variations found in severe hemophilia A patients, but only a few deletion breakpoints have been characterized precisely. Objectives: Resolving at the nucleotide level 24 F8 large deletions to provide new data on the mechanisms involved in these rearrangements. Methods: Breakpoint junctions of 24 F8 large deletions were characterized using a combination of long‐range polymerase chain reaction, whole F8 NGS sequencing, and Sanger sequencing. Repeat elements, non‐B DNA, and secondary structures were analyzed around the breakpoints. Results: Deletions ranged from 1.667 kb to 0.5 Mb in size. Nine involved F8 neighboring genes. Simple blunt ends and 2–4 bp microhomologies were identified at the breakpoint junctions of 10 (42%) and 8 (33%) deletions, respectively. Five (21%) deletions resulted from homeologous recombination between two Alu elements. The remaining case corresponded to a more complex rearrangement with an insertion of a 19 bp‐inverted sequence at the junction. Four different breakpoints were located in a 562‐bp region in F8 intron 6. This finding suggested that this region, composed of two Alu elements, is a DNA breakage hotspot. Non‐B DNA and secondary structures were identified in the junction regions and may contribute to DNA breakage. Conclusion: Molecular characterization of deletion breakpoints revealed that non‐homologous non‐replicative DNA repair mechanisms and replication‐based mechanisms seemed to be the main causative mechanisms of F8 large deletions. Moreover, we identified a possible F8 DNA breakage hotspot involved in non‐recurrent rearrangements.